A Hilbert Transform Based Shear Wave Speed Estimation Method for Shear Wave Elasticity Imaging - Hassan, Mohammed A; Salem, Nancy M; El-Adawy, Mohamed I (British Journal of Healthcare and Medical Research, 2016)
In this paper, a Hilbert transform based method is used to estimate shear wave speed. Shear wave speed can be measured from the lateral propagation of particle displacements or velocities within the tissue, these particle displacements or velocities are generated by simulating radio frequency signals measured from ultrasound probe elements that image the displaced particles generated from a finite-element model (FEM) that simulates the dynamic response of tissues to acoustic radiation forces. The proposed shear wave speed estimation method is based on locating a zero-amplitude crossing in the Hilbert transform of the cross-correlation function between the particle displacement measured at first lateral location greater than the lateral width of shear wave and the displacement measured and subsequent lateral lines under examination at a certain depth. The results obtained from this method is compared to the lateral Time to Peak (TTP) method that finds the instance at which the maximum displacement is detected at each lateral location under examination at a certain depth. The proposed algorithm reveals a reconstruction of materials having shear modulus of 1.43±0.20, 2.92±0.39, 4.09±0.54, 8.13±1.06, 12.11±1.52, 16.16±2.08 kPa on particle displacement signals for 1.33, 2.835, 4, 8, 12, and 16 kPa shear moduli materials respectively and 1.34±0.40, 2.66±0.41, 3.77±0.58, 7.45±1.14, 11.34±1.51, and 14.90±2.08 kPa on particle velocity signals for 1.33, 2.835, 4, 8, 12, and 16 kPa shear moduli materials respectively. Finally, the proposed method is based on locating a zero-amplitude crossing in the Hilbert transform of the cross-correlation function appears to provide more accurate results than Lateral TTP method.